Difference between revisions of "Simplify Command"

From GeoGebra Manual
Jump to: navigation, search
(command syntax: changed [ ] into ( ))
m
 
(One intermediate revision by the same user not shown)
Line 11: Line 11:
 
== CAS Syntax ==
 
== CAS Syntax ==
 
;Simplify( <Function> ):Simplifies the terms of the given function, if possible. Undefined variables can be included in the terms.  
 
;Simplify( <Function> ):Simplifies the terms of the given function, if possible. Undefined variables can be included in the terms.  
:{{example|1=<code><nowiki>Simplify(3 * x + 4 * x + a * x)</nowiki></code> yields ''xa'' + ''7x''.}}
+
 
:{{Note|1=See also [[Factor Command]].}}
+
:{{examples|<div>
 +
:*<code><nowiki>Simplify(3 * x + 4 * x + a * x)</nowiki></code> yields <code> ''a x'' + ''7x''</code>.
 +
:*<code><nowiki>Assume(x<2,Simplify(sqrt(x-2sqrt(x-1))))</nowiki></code> yields <code>-sqrt(abs(x - 1)) + 1</code>
 +
:*<code><nowiki>Assume(x>2,Simplify(sqrt(x-2sqrt(x-1))))</nowiki></code> yields <code>sqrt(x - 1) + 1</code></div>}}
 +
:{{Note|1=See also [[Factor Command]], [[Assume Command]], [[PartialFractions Command]], [[Expand Command]], [[Polynomial Command]].}}

Latest revision as of 21:33, 15 May 2019


Simplify( <Function> )
Simplifies the terms of the given function, if possible.
Example: Simplify(x + x + x) yields the function f(x) = 3x.
Simplify( <Text> )
Attempts to tidy up text expressions by removing repeated negatives etc.
Example: For a = b = c = -1 Simplify("f(x) = " + a + "x² + " + b + "x + " + c) yields the text f(x) = -x2 - x - 1.
Note:
The FormulaText Command normally produces better results and is simpler.
Note:
This command needs to load the Computer Algebra System, so can be slow on some computers. Try using the Polynomial Command instead.

CAS Syntax

Simplify( <Function> )
Simplifies the terms of the given function, if possible. Undefined variables can be included in the terms.
Examples:
  • Simplify(3 * x + 4 * x + a * x) yields a x + 7x.
  • Assume(x<2,Simplify(sqrt(x-2sqrt(x-1)))) yields -sqrt(abs(x - 1)) + 1
  • Assume(x>2,Simplify(sqrt(x-2sqrt(x-1)))) yields sqrt(x - 1) + 1
© 2024 International GeoGebra Institute